Health and Medical Informatics Education - Haux, R.; Leven, F. J.; Moehr, J. R.; Protti, D. J. (Methods of Information in Medicine, 1994)
Health and medical informatics education has meanwhile gained considerable importance for medicine and for health care. Specialized programs in health/medical informatics have therefore been established within the last decades.This special issue of Methods of Information in Medicine contains papers on health and medical informatics education. It is mainly based on selected papers from the 5th Working Conference on Health/Medical Informatics Education of the International Medical Informatics Association (IMIA), which was held in September 1992 at the University of Heidelberg/Technical School Heilbronn, Germany, as part of the 20 years’ celebration of medical informatics education at Heidelberg/Heilbronn. Some papers were presented on the occasion of the 10th anniversary of the health information science program of the School of Health Information Science at the University of Victoria, British Columbia, Canada. Within this issue, programs in health/medical informatics are presented and analyzed: the medical informatics program at the University of Utah, the medical informatics program of the University of Heidelberg/School of Technology Heilbronn, the health information science program at the University of Victoria, the health informatics program at the University of Minnesota, the health informatics management program at the University of Manchester, and the health information management program at the University of Alabama. They all have in common that they are dedicated curricula in health/medical informatics which are university-based, leading to an academic degree in this field. In addition, views and recommendations for health/medical informatics education are presented. Finally, the question is discussed, whether health and medical informatics can be regarded as a separate discipline with the necessity for specialized curricula in this field.In accordance with the aims of IMIA, the intention of this special issue is to promote the further development of health and medical informatics education in order to contribute to high quality health care and medical research.
Keywords: Health Informatics Education; Medical Informatics Education